Preparation and characterization of mortar mixes containing organic acid/expanded vermiculite composite PCM - Xinzhong Zhang; Weizhun Jin; Yajun Lv; Haibin Zhang; Weibing Zhou; Fangyi Ding (Functional Materials, 2017)
In this paper, capric acid (CA) and palmitic acid (PA) binary PCM/expanded vermiculite (CA-PA/EVM) form stable composite PCM (FS-CPCM) was firstly synthesized by adsorption method. The EVM had the optimal adsorption rate when the mass ratio of CA-PA to EVM was 45:55. The FT-IR results indicated that there was no chemical reaction between binary PCM and EVM. After the thermal cycles for 50 times, the mass loss of the prepared CA-PA/EVM FS-CPCM was 2.8%. However, the latent heat was reduced by 16.10%. Furthermore, thermal energy storage (TES) mortar mixes were prepared by replacing sand aggregates with the fabricated CA-PA/EVM FS-CPCM. The effect of replacing sand aggregates with CA-PA/EVM FS-CPCM on compressive and flexural strength of the mortar mixes was investigated by mechanical experiments. The prepared mortar mixes with CA-PA/EVM FS-CPCMs aggregate exhibited good thermal performance and could be preferentially potential PCM for thermal regulation and energy saving in buildings.